2020
DOI: 10.1021/acs.chemmater.0c00528
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbosilane-Grafted Nanoparticles: Free-Flowing Hairy Nanoparticle Liquids That Convert to Ceramic

Abstract: Here, we report a new class of hybrid nanoparticles (NPs) that are self-supporting and display viscous flow behavior in the absence of solvent, yet convert to a purely inorganic material on heating. Hairy nanoparticles (HNPs) composed of silica nanoparticle cores (10−20 nm diameter) and preceramic poly(1,1-dimethylpropylsilane) (l-PCS) brushes were synthesized via a grafting-from approach utilizing hydrosilylation chemistry. The l-PCS polymer brush was grown from the nanoparticle core by anchoring the Pt(0) Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 76 publications
(134 reference statements)
2
27
0
Order By: Relevance
“…After silanization, SiH–ghosts were functionalized by either a graft-to reaction with SMP-10 or a graft-from reaction with ADS (Figure ). Functionalization with ADS results in poly­(ADS), a polymer with a well-known structure. However, previous work has shown that poly­(ADS) has a low ceramic yield .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After silanization, SiH–ghosts were functionalized by either a graft-to reaction with SMP-10 or a graft-from reaction with ADS (Figure ). Functionalization with ADS results in poly­(ADS), a polymer with a well-known structure. However, previous work has shown that poly­(ADS) has a low ceramic yield .…”
Section: Resultsmentioning
confidence: 99%
“… Functionalization with ADS results in poly­(ADS), a polymer with a well-known structure. However, previous work has shown that poly­(ADS) has a low ceramic yield . Functionalization with SMP-10 has the benefit of using a commercially available material with high ceramic yields, approaching 80% according to the manufacturer, but is prone to cross-linking between polymer chains due to the allyl groups and SiH groups present in the polymer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported the first example of using hydrosilylation to graft preceramic polymers from nanosilica. 34 Hydrosilylation is a straightforward route toward the fabrication of poly(1,1-dimethylpropylsilane)-grafted silica particles, and these particles are very dispersible in organic solvents. Solvent removal revealed a stable free-flowing composite with low viscosity compared to a physical mixture of poly(1,1-dimethylpropylsilane) and silica nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%